The Old, the New, and the Used One—Assessing Legacy in Family Firms - Alexandrina Maria Pauceanu; Rodica Milena Zaharia; Melisa Petra Benchis (Administrative Sciences)
The current study aims to determine the meaning and the role of legacy in the development of family businesses from the perspective of multigenerational family businesses. Employing Thematic Analysis (TA) and Gioia methodology, the transcript of in-depth interviews with representatives of five family businesses, from different industries (military products and wine, banking and jewelry) were analyzed and checked against the literature. The findings show that legacy is a complex process that evolves not only from its core elements, but as a part of business involvement in society. According to these elements, there are four patterns of legacy, namely legacy of knowledge, legacy of values, legacy of relationships, and legacy of contribution to society. These four patterns of legacy determine a specific type of doing business: “Sustainability Stewards”, “Knowhow Handover”, “Values Inheritance”, and “Intergenerational Blueprint”. Each type corresponds to a unique approach to managing and preserving the legacy within the family business. A set of best practices that family businesses seeking to consolidate their legacy is proposed as a practical value of this study.